Pharmacokinetics and milk excretion pattern of eprinomectin at different dose rates in dairy cattle - Ballent, Mariana (2021)
This study aimed at determining the plasma disposition kinetics of eprinomectin (EPM) and EPM excretion pattern through milk after topical administration to dairy cattle at the recommended dose of 0.5 mg/kg and at 1 and 1.5 mg/kg. A high variability in the plasma concentration profiles was observed among animals, particularly in the Cmax values, with a coefficient of variation between 39 and 53%. The Cmax and AUC values were significantly affected by the dose administered at 1.5 mg/kg. However, such differences did not seem to follow a linear pattern among treatments. These parameters did not differ among dose rates after dose normalization; nevertheless, the simulation of a linear kinetic disposition showed a mean plasma AUC value of 254 ng.d/ml instead of the observed value of 165 ng.d/ml. EPM concentration profiles in milk were significantly lower than those measured in plasma. The Cmax and AUC milk-to-plasma ratios ranged from 0.14 to 0.26 and 0.16 to 0.21, respectively (p>0.05). The low milk-to-plasma ratio of EPM accounted for a low percentage of the fraction of the administered dose excreted through milk, being significantly higher at a dose rate of 0.5 mg/kg (0.07%) of EPM than at 1.5 mg/kg (0.04%) (p<0.05). The topical administration of EPM to lactating dairy cows at higher doses than that recommended for gastrointestinal nematodes showed a milk excretion pattern with a zero milk withdrawal period. In conclusion, the administration of topical EPM formulation at 1 or 1.5 mg/kg may be a valuable tool to be used in regional strategic deworming programs aimed to control ectoparasite infections in dairy production systems.